Validity of the Brunel Mood Scale for use with UK, Italian and Hungarian Athletes - Lane, A. M.; Soos, I.; Leibinger, E.; Karsai, I.; Hamar, P. (Hot topics in sports and athletics, 2008)
The present study investigated the factorial validity of the Brunel Mood Scale for use with UK, Italian and Hungarian athletes. One thousand five hundred and eleven mood responses from athletes were analysed using Confirmatory Factor Analysis (CFA). CFA on the Italian, Hungarian and UK athletes were close to the .90 criterion for acceptable fit initially highlighted by Bentler (1990), but below the .95 fit index suggested by Hu and Bentler (1995). It is argued that CFA results lend some support for the proposed validity of an eight-factor and 32-item mood scale. However, as the fit index was marginal, further work was needed. Eight separate CFAs on each subscale indicated acceptable fit indices for each factor. As confusion is a cognitive rather than affective construct, we decided to remove confusion and re-analyse data on a 21-item and seven-factor scale. CFA results on the 21-item and seven-factor scale indicated fit indices over .90, hence an improvement over the 32-item version. In conclusion, the 21-item and 32-item BRUMS represent a theoretically and empirically supported approach to investigating mood for use in UK, Hungarian and Italian athletes.